Campanian Calciturbidites from Northeast Iraq, Kurdistan Region: Insight into Paleogeography and Source Areas of the Shiranish Formation - Kamil, Anhar I.; Al-Dulaimi, Salam; Karim, Kamal Haji (Iraqi Journal of Science, 2021)
Calciturbidites are similar to siliciclastic turbidites in structure, texture, basin physiography and processes of deposition; nevertheless, their clasts (grains) are carbonate minerals. Turbidity currents transport carbonate grains from carbonate source areas and coastal areas to the deep basins after passing the shelf (peri-platform). These currents are triggered by short-lived catastrophic events, such as tsunamis, earthquakes, marine slides, and typhoons. The Late Cretaceous Zagros Foreland and Hinterland in NE-Iraq (Kurdistan Region) was an active source for the shedding of voluminous sediments to the deep basin of Zagros Foreland Basin. During late Campanian, Shiranish Formation was deposited in the foreland basin; it occurs in the most famous oil fields in the Middle East and represents hemplagite facies (much diluted turbidite facies). Previous studies have not broached the origins of Shiranish Formation, neither in detail or briefly. Conversely, the present study focused on linking the calciturbidite system to the origin of the deposition of the Shiranish Formation via derivation from main carbonate source areas. Along long distance, the sediments crossed the marginal slope, scoring submarine channels and depositing coarse detrital carbonates before reaching the basin plain. On the plain, mostly the fine fractions have settled down and mixed with pelagic sediment. The calciturbidite evidence could be tracked for more than 40 km in the studied area from the slope and outer shelf (present Thrust Zone) to the basin plain (High Folded zone). In several places, channelized detrital laminated limestones are found inside Shiranish Formation and in the most proximal area near Qaladiza town. Bouma sequences are clearly observable with erosional base and A, B, and C divisions. These calciturbidites are keys for picturing Campanian paleogeography and nature of the source area which was consisted of limestone.